2020
DOI: 10.1186/s12873-020-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics, triage utilisation, level of care, and outcomes in an unselected adult patient population seen by the emergency medical services: a prospective observational study

Abstract: Background: Crowding in the emergency department (ED) is a safety concern, and pathways to bypass the ED have been introduced to reduce the time to definitive care. Conversely, a number of low-acuity patients in the ED could be assessed by the emergency medical services (EMS) as requiring a lower level of care. The limited access to primary care in Sweden leaves the EMS nurse to either assess the patient as requiring the ED or to stay at the scene. This study aimed to assess patient characteristics and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 49 publications
7
59
1
Order By: Relevance
“…Overall, 11% of our study patients died within 30 days, similar to previous studies [8,9]. The mortality risk was almost three times as high as in the total EMS population in the same area [19]. Furthermore, our result also found that men with dyspnoea as the main symptom had a higher mortality rate than women.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, 11% of our study patients died within 30 days, similar to previous studies [8,9]. The mortality risk was almost three times as high as in the total EMS population in the same area [19]. Furthermore, our result also found that men with dyspnoea as the main symptom had a higher mortality rate than women.…”
Section: Discussionsupporting
confidence: 90%
“…Older adult non-conveyed patients were more often assessed with nonspeci c or vague presenting symptoms than younger patients. In line with a previous study [3], patients assessed with nonspeci c presenting symptoms were at higher risk of ED visits and hospitalisation following nonconveyance. Conditions related to infectious diseases, such as sepsis, have high mortality rates among older adult patients [28].…”
Section: Discussionsupporting
confidence: 87%
“…By its very nature, the ambulance service constitutes a high-risk patient safety environment which provides round-the-clock, year-round care services to a large volume of patients with a wide range of medical complaints [1]. Patients who are not transported to the hospital after an initial assessment by ambulance clinicians, that is, non-conveyed patients in the ambulance service [2], represent a signi cant and increasing proportion of those who seek ambulance services [3][4][5]. The research on patient outcome following non-conveyance is relatively sparse and, to some extent, has contrasting results [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland, previous studies show that approximately 40% of EMS missions do not lead to patient conveyance to a healthcare facility [6,7]. Globally these rates are, for example, 19,7% in Sweden [8], 12,9% in Denmark [9], 37.5% in England [10], 26.2% in Netherlands [11] and 15.5% in Australia [12].…”
Section: Introductionmentioning
confidence: 99%